Losio Antioksidan Buah Naga Merah (Hylocereus polyrhizusBritton and Rose) - Sinaga, Amanda Angelina; Luliana, Sri; Fahrurroji, Andhi (UI Scholars Hub, 2015)
Hylocereus polyrhizus Britton and Rose (Red dragon fruit) has been shown to have antioxidant activity which contains vitamin C, polyphenol, and flavonoid. This research was aimed to investigate antioxidant activity from H. polyrhizus in form of lotion. Lotion were made with 5 concentration from H. polyrhizus methanol extract were 0.04, 0.08, 0.16, 0.32 and 0.64%. Lotion antioxidant activity was measured using DPPH method. The result showed that H. polyrhizus methanol extract had antioxidant activity with inhibition concentration were 19.99±0.33; 25.01±0.08; 39.14±0.04; 66.69±0.12 and 83.37±0.05. The result showed significant differences on antioxidant activity. The physical stability observation of five formula with cycling test method showed unstability because of discolouration (oxidation). As well as the methods of mechanical test showed unstability of lotion because saponification process.